Self-injectable epinephrine: doctors' attitude and patients' adherence in real-life. Issue 5 (October 2020) - Carrillo-Martin, Ismael; Caminati, Marco; Tanno, Luciana K.; Gonzalez-Estrada, Alexei
Abstract : Purpose of review: Epinephrine is the only life-saving treatment of anaphylaxis. Prescription and administration rates of self-injectable epinephrine are generally low. It is unclear whether this is because of availability, low prescription rates, fear of using epinephrine, or a combination of these issues. Recent findings: This review focuses on what self-injectable epinephrine devices (SIED), such as auto-injectors and prefilled syringes, are preferred by patients and healthcare professionals (HCP). Our findings suggest that a device's ease to use, proper and frequent training on its operability, and availability have an impact on preferences and adherence to treatment with SIEDs. After prescribing a patient with a SIED, clinicians should emphasize its use in anaphylaxis, educate patients/caregivers to identify anaphylaxis and on how to use the SIED, and encourage constant practicing with training devices. Summary: Epinephrine is the sole recommended anaphylaxis treatment and SIEDs are of critical usefulness in the community setting. Further studying of these devices is needed to optimize education for HCPs and patients and their accessibility to SIEDs.